A new genus and species of Cheyletidae (Acariformes: Prostigmata) from citrus trees in Florida - Xia, Bin; Klompen, Hans; Childers, Carl C. (Zootaxa, 2011)
A new genus and species, Lanceacheyla whartoni (Acariformes: Prostigmata: Cheyletidae) is described for the female, male, and teleonymph. All mites were collected from leaves of ‘Hamlin’ orange trees in Florida, U.S.A. Affinities of the new genus within Cheyletidae are discussed.